2023
DOI: 10.3389/fpsyg.2023.1071936
|View full text |Cite
|
Sign up to set email alerts
|

Differences in central symptoms of anxiety and depression between college students with different academic performance: A network analysis

Abstract: ObjectiveThe prevalence of anxiety and depressive symptoms for Chinese college students are high. Academic pressure is one of the prominent risk factors of psychological well-beings for Chinese college students. The application of network analysis provides researchers a more comprehensive understanding of symptom-symptom interaction in mental disorders. This study aims to find out whether there is a difference in central symptoms between students with different academic performance.MethodA total sample of 1,29… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…17 Furthermore, it has been reported that the internalising symptoms exhibited by students differ depending on their educational performance. 30 Depression was the predominant symptom in students with low educational performance, whereas anxiety (or uncontrolled worry) was the predominant symptom in students with good educational performance. 30 Additionally, students with mental health issues infrequently seek support, which is considered a major barrier to the implementation of suicide prevention programmes.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…17 Furthermore, it has been reported that the internalising symptoms exhibited by students differ depending on their educational performance. 30 Depression was the predominant symptom in students with low educational performance, whereas anxiety (or uncontrolled worry) was the predominant symptom in students with good educational performance. 30 Additionally, students with mental health issues infrequently seek support, which is considered a major barrier to the implementation of suicide prevention programmes.…”
Section: Discussionmentioning
confidence: 96%
“…30 Depression was the predominant symptom in students with low educational performance, whereas anxiety (or uncontrolled worry) was the predominant symptom in students with good educational performance. 30 Additionally, students with mental health issues infrequently seek support, which is considered a major barrier to the implementation of suicide prevention programmes. 2,31 Therefore, to effectively support students who are suffering from underachievement or worried about their future, their parents, schools and community need to make efforts to observe, detect and implement measures more widely.…”
Section: Discussionmentioning
confidence: 96%
“…According to a metaanalytic paper (Brumariu et al, 2023), anxiety is not a significant impediment to academic achievement, although it is a crucial factor associated with dropout rates and academic self-concept. Similarly, a recent network analysis of college students' crosssectional data (Wang et al, 2023) reports that feeling depressed was the most central symptom for those with a bottom 27% grade point average.…”
Section: Nomophobia As a Predictor Of Depression And Anxietymentioning
confidence: 89%
“…Following previous studies ( Mullarkey et al, 2019 ; Peng et al, 2023 ; Wang et al, 2023 ), we performed network analysis in the depression group ( N = 705) to explore the central symptoms and key edges of depression among Chinese OD nurses. Network analyses were conducted using bootnet ( Epskamp et al, 2018a ) and qgraph ( Epskamp et al, 2012 ) packages in R program (version 4.1.2).…”
Section: Methodsmentioning
confidence: 99%